Tongue condyloma: presentation of a case report and literature review: Condiloma viral en lengua: presentación de un caso clínico y revisión bibliográfica - Rozas-Llerena, Rubén (2019)
Condyloma acuminatum is a sexually transmitted disease caused by the papilloma virus(HPV) It is frequently found in the ano-genital region and is uncommon in the oral cavity.However, the increase in oral sexual activity has further favored the appearance of HPV in theoral mucosa. This report describes a condyloma in the oral cavity (tongue) of a 43-year-old man withhistory of oral sexual practice, whose diagnosis was confirmed by a biopsy.   DOI 10.25176/RFMH.v19.n1.1799